Frontispiece: Morphology‐Reserved Synthesis of Discrete Nanosheets of CuO@SAPO‐34 and Pore Mouth Catalysis for One‐Pot Oxidation of Cyclohexane. Issue 7 (3rd February 2020) - Guo, Xiangke; Xu, Mengxia; She, Minyi; Zhu, Yan; Shi, Taotao; Chen, Zhaoxu; Peng, Luming; Guo, Xuefeng; Lin, Ming; Ding, Weiping
Abstract : Heterogeneous Catalysis In their Communication on page 2606, X. F. Guo, M. Lin, W. P. Ding et al. describe the synthesis of 2D nanosheets of CuO on nano‐zeolite as catalyst for the selective oxidation of cyclohexane to adipic acid using O2 as oxidant.